Management and effect of platelet-rich plasma on wound healing: small reality of Oglio Po Hospital - Follo, Fioralba; Dejana, Dario Oliver; Belletti, Marzia; Bongiovanni, Nicolina; Scarpa, Giuseppina; Pezzali, Patrizia; Borsi, Sandra; Sanfilippo, Laura; Lusetti, Nadia; Zaini, Luigi; Loritto, Patrizia; Pogliacomi, Francesco; et al. (Acta Biomedica Atenei Parmensis, 2017)
Platelet Rich Plasma (PRP) represents a relatively new approach in regenerative medicine. Its use is increasing in the treatment of a variety of orthopedic conditions, such as the management of acute wounds, chronic non-healing lesions, acceleration of bone formation, tendinopathy and chondropathy. The Orthopaedic Unit at Oglio Po Hospital uses PRP Gel in wound care since 2008. More than 70 patients have been treated with this procedure. The aim of this study is to show our patients outcome. We present 3 cases of severe traumatic wound treated with our PRP protocol. The patients had complete healing of the lesion with good aesthetic results.